2009
DOI: 10.1002/dac.1098
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of data scheduling algorithms for multi‐item requests in multi‐channel broadcast environments

Abstract: SUMMARYNowadays querying multiple-dependent data items in a request is common in many advanced mobile applications, such as traffic information enquiry services. In addition, multi-channel architectures are widely deployed in many data dissemination systems. In this paper, we extend a number of data productivity-based scheduling algorithms and evaluate their performance in scheduling multi-item requests in multi-channel broadcast environments. We observe from the experimental results two performance problems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…K. Liu et al [21] presented the DUP algorithm which considers both the urgencies of queries and data items, and the DUP algorithm always broadcasts the most urgent data item which is required in the most urgent query. A much more comprehensive discussion on recent research results can be found in [22]. Lv et al introduced the concept of profit into the broadcast schedule and proposed an efficient scheduling algorithm in [23] which always choose the data item with highest profit to be broadcast at each time unit.…”
Section: Related Workmentioning
confidence: 98%
See 1 more Smart Citation
“…K. Liu et al [21] presented the DUP algorithm which considers both the urgencies of queries and data items, and the DUP algorithm always broadcasts the most urgent data item which is required in the most urgent query. A much more comprehensive discussion on recent research results can be found in [22]. Lv et al introduced the concept of profit into the broadcast schedule and proposed an efficient scheduling algorithm in [23] which always choose the data item with highest profit to be broadcast at each time unit.…”
Section: Related Workmentioning
confidence: 98%
“…A time-critical request is associated with a deadline imposed by either the application or the user, the result of a request is useful only if all the required data items can be received before the deadline. For such kind of applications, some real-time broadcast scheduling algorithms have been proposed [14], [6], [22], which take queries' deadlines into account. But unfortunately, almost all the existing real-time broadcast scheduling algorithms only support single data item [2] or one-shot queries [7], [16], and thus can be of low performance, or even not applicable in some practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless technologies, such as radio frequency identification and GPS, have been applied for facilitating instructional processes by creating a highly interactive environment [7,8]. A system was developed to support the foreign language learning.…”
Section: Applied Technologies In U-learning Environmentsmentioning
confidence: 99%
“…However, this solution is infeasible in a business environment. Although a router can schedule the transmission of each file, the schedule does not indicate the value of the file to the business (Liu and Lee 2010). For example, the system cannot determine whether a non-urgent file sent by the Chief Executive Officer is more important than an urgent file sent by a project manager.…”
Section: Introductionmentioning
confidence: 96%